FEATURES OF ADAPTATION OF FUTURE SPECIALISTS OF FIRE AND RESCUE SERVICE TO THE CONDITIONS OF PROFESSIONAL ACTIVITY (Pedagogy of Higher and Secondary Education, 2009)
The problem of cadets' adaptation to the conditions of professional activity of fire-resque servise.
Keywords: activity; adaptation; professional activity; fire-rescue station; commander of the guard